2022
DOI: 10.1108/lht-06-2021-0198
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric study on library and information science and information systems literature during 2010–2019

Abstract: PurposeStudying the nature of research progress in interrelated research domains is important for evaluating the research productivity and to understand the current trends of the area of research. This study aims to examine a research domain that combines library and information science with information systems (IS).Design/methodology/approachQuartile 1 journals that cover both subject domains in SCImago were selected for the study. Bibliographic records of the publications during 2010 and 2019 were retrieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…The explanation was carried out on various articles in national and international journals related to the role of technology in era 5.0 in Arabic language learning, which was analyzed through supporting literature libraries and data collected using words. The discussion in this article uses a library research design where the data sources of this research are books and national and international journals, and other library sources (Wijewickrema, 2022). And in this study, data collection was obtained from books and online journals.…”
Section: Methodsmentioning
confidence: 99%
“…The explanation was carried out on various articles in national and international journals related to the role of technology in era 5.0 in Arabic language learning, which was analyzed through supporting literature libraries and data collected using words. The discussion in this article uses a library research design where the data sources of this research are books and national and international journals, and other library sources (Wijewickrema, 2022). And in this study, data collection was obtained from books and online journals.…”
Section: Methodsmentioning
confidence: 99%
“…(2023) studied the extent of the development of LIS research using Barnett aging model and suggested that the LIS field was aging slowly and reached a relatively mature stage. On the other hand, Wijewickrema (2023) also studied LIS and information systems together as a research domain using Quartile 1 Journals from SCIMago from 2010 to 2019 and data obtained from the Scopus database using VOSviewer data visualization tools. Readers may also be interested in other LIS-related bibliometric studies, such as the study by Nwankwo et al .…”
Section: Bibliometric Analytics For Research Topicsmentioning
confidence: 99%
“…Ding et al (2021) analyzed the characteristics of knowledge diffusion of LIS from the perspective of citation. Wijewickrema (2022) also provided a LIS bibliometric study on literature from 2010 to 2019. Notably, Kim et al (2021) studied the scientific profile and knowledge diffusion of this journal.…”
Section: Research Trends Of Library and Information Science (Lis) And...mentioning
confidence: 99%